ANALYSIS ON “THE BRIDGE ENGLISH COMPETENCE”, STUDENT TEXTBOOK FOR GRADE IX JUNIOR HIGH SCHOOL, BASED ON SCHOOL BASED CURRICULUM - MURNIATI, SILIH (2010)
This researcher paper is mainly intended to find out whether or not the English textbook used for the ninth year students of Junior High School "The Bridge English Competence" compatible with indicators of the language skill suggested by School Based Curriculum.